Onosma zagrica (Boraginaceae), a new species from Iran - Dehshiri, Mohammad Mehdi (Phytotaxa, 2018)
A new species of Onosma sect. Onosma L. (Boraginaceae), O. zagrica Dehshiri, is described and illustrated from the western part of Iran from Khargushan Mountain near the Khorramabad city (Lorestan Province). The new species differs from Onosma kilouyensis Boiss. & Hausskn. in being a smaller plant, 1.4–3 × 0.25–0.7 cm, narrowly elliptic or linear-lanceolate cauline leaf, longer pedicels, yellow or at first cream, then blue corolla, and smaller nutlet. The IUCN threat category of O. zagrica is determined as “CR (Critically Endangered)”.